Brazil : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Brazil. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
Economic performance has been much better than expected, in part due to the authorities' forceful policy response. Nevertheless, Brazil's long-standing challenges of low growth, high debt, and elevated levels of poverty and inequality have been exacerbated by the pandemic. Tragically, more than 550,000 Brazilians have died from COVID-19.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Brazil